Analisis Peluang Strategi Usaha dan Persepsi Harga terhadap Kepuasan Pelanggan Lada Hitam Rooster - Anita Sulistiani; Berkey Tabitha Vahrya Anam; Gita Fitri; Velian Felent Inestania Clarita; Muhammad Fhasa Ardibillah; Muhammad Irvan; Emmywati (PUTRA JAWA PUBLISHER, 2023)
The purpose of this study is to talk about the prospects and business options available to Black Rooster Pepper. In this particular study, the strategy of interviewing customers directly about their experiences with black rooster pepper was adopted. According to the findings, actors in the business world need to be able to generate new changes and innovations within their companies, which should be capable of generating new opportunities and markets. The marketing plan that is being used makes use of the unique flavor of the black rooster pepper that is being sold in conjunction with the reasonable price that must be paid.